Effect of herbivore load on VOC-mediated plant communication in potato - Carla Vázquez-González; Violeta Quiroga; Lucía Martín-Cacheda; Rasmann, Sergio; Röder, Gregory; Luis Abdala-Roberts; Xoaquín Moreira (My University, 2023)
Herbivore-damaged plants emit volatile organic compounds (VOCs) that can alert neighbours and boost their resistance. While VOC-mediated plant communication has been shown to be herbivore-specific, we know little about its contingency on variation in herbivore load. To address this knowledge gap, we tested herbivore load effects on VOC-mediated communication between potato plants (Solanum tuberosum) using the generalist herbivore Spodoptera exigua. First, we tested whether herbivore load (three levels: undamaged control, low, and high load) affected total VOC emissions and composition. Second, we matched emitter and receiver plants and subjected emitters to the same herbivore load treatments. Finally, we performed a bioassay with S. exigua on receivers to test for induced resistance due to VOC-mediated communication. We found that herbivory significantly increased total VOC emissions relative to control plants, and that such increase was greater under high herbivore load. In contrast, we found no detectable effect of herbivory, regardless of the load, on VOC composition. The communication experiment showed that VOCs released by herbivore-induced emitters boosted resistance in receivers (i.e., lower leaf damage than receivers exposed to VOCs released by control emitters), but the magnitude of such effect was similar for both levels of emitter herbivore load. These findings suggest that changes in VOCs due to variation in herbivore load do not modify the outcomes of plant communication.